Sentiment Analysis of the Role and Connotation of Office Secretary through Twitter - Rouna Paoki; Jimmy H Moedjahedy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
A secretary is responsible for coordinating and attending board and committee meetings, producing minutes, acting as a liaison between directors, officers, and shareholders, and directing activities related to the annual shareholders' meeting. The presence of sexual harassment or an intimate relationship with a married supervisor is one of the challenges a woman encounters at work. Consequently, the secretary role and the term secretary are frequently used negatively. This research seeks to do a Twitter-based sentiment analysis of the secretary's words and position. Using the Tweppy API, the sentiment analysis method was applied to the research by analyzing phrases on Twitter. This investigation makes use of five keyword instances. There are 31.73 percent favorable answers to scenarios involving the words "boss-secretary," 29.72 percent negative responses, and 38.55 percent neutral replies. There are 45.97% positive answers, 19.18% negative responses, and 34.85% neutral responses to scenarios containing the keyword "secretary position." 42.11 percent of answers to scenarios including the keyword "female secretary" are favorable, 17.22 percent are negative, and 40.67 percent are neutral. 35.44 percent of replies to scenarios including the keyword "office secretary" are positive, 17.84 percent are negative, and 46.72 percent are neutral. Responses to the fifth scenario were 36.60 percent positive, 19.35 percent negative, and 44.06 percent neutral. According to the results of the sentiment analysis of the five scenarios containing varied keywords, the negative connotations in each scenario never outweigh the positive ones. Each scenario indicates that the proportion of positive response values is consistently more significant than the proportion of negative response values. This implies that the word secretary and the office position of secretaries continue to trigger positive feelings from users.